2020
DOI: 10.1111/mpp.13010
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis small G‐protein AtRAN1 is a positive regulator in chitin‐induced stomatal closure and disease resistance

Abstract: Plants coexist with diverse microorganisms, and their interactions have resulted in coevolution. Higher plants have immune systems with two different levels to resist pathogen invasion and multiplication. The gene-for-gene concept characterizes genetic control by plant resistance gene products and pathogen avirulence proteins, which are pathogen-secreted effectors that manipulate host processes in favour of the pathogen (Goehre & Robatzek, 2008; Gouveia et al., 2017; Wang et al., 2019); their direct or indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…However, compared with the WT, atran1, Col-0&AtRAN1 Q72L -OE and atran2/3&AtRAN1 Q72L -OE plants exhibited severe chlorosis and necrotic cell death, but the AtRAN1-OE plants exhibited lower levels of chlorosis and necrotic cell death (Figure 5a,d). Interestingly, we found that the atran1 mutant was also more susceptible to the bacterial pathogen with higher ion leakage and lower chlorophyll content than Col-0 after Pst infection (Figure 5b-d), in agreement with a previous report (Song et al, 2020). To further investigate whether the necrotic cell death induced by Pst was related to the accumulation of reactive oxygen species (ROS), 3,3 0 -diaminobenzidine (DAB) staining was used to detect H 2 O 2 in WT, AtRAN1-OE, and AtRAN1 Q72L -OE plants after inoculation with Pst (Figure 5b and Figure S9).…”
Section: Atran1 Overexpression Results In Enhanced Resistance To P Syringae Dc3000 Infectionsupporting
confidence: 93%
“…However, compared with the WT, atran1, Col-0&AtRAN1 Q72L -OE and atran2/3&AtRAN1 Q72L -OE plants exhibited severe chlorosis and necrotic cell death, but the AtRAN1-OE plants exhibited lower levels of chlorosis and necrotic cell death (Figure 5a,d). Interestingly, we found that the atran1 mutant was also more susceptible to the bacterial pathogen with higher ion leakage and lower chlorophyll content than Col-0 after Pst infection (Figure 5b-d), in agreement with a previous report (Song et al, 2020). To further investigate whether the necrotic cell death induced by Pst was related to the accumulation of reactive oxygen species (ROS), 3,3 0 -diaminobenzidine (DAB) staining was used to detect H 2 O 2 in WT, AtRAN1-OE, and AtRAN1 Q72L -OE plants after inoculation with Pst (Figure 5b and Figure S9).…”
Section: Atran1 Overexpression Results In Enhanced Resistance To P Syringae Dc3000 Infectionsupporting
confidence: 93%
“…4B ). Considering that the chitin-triggered immunity pathway is involved in stomatal regulation, 55 we suspect that this pathway may also regulate drought response in V. mangachapoi .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, AtRAN1 might positively regulate drought responses by mediating other stress response genes. 55 As the possibility of fungal infection in the samples used for the transcriptomic analyses cannot be completely excluded, it is unclear whether the increased expression of chitin-triggered genes was solely the result of drought stress or if fungal infection was involved, as well. However, since drought stress is tightly linked with susceptibility to infection, 55 genes responsible for stomatal control are likely involved in both abiotic and biotic stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a sessile lifestyle, plants are constantly confronted with various biotic stresses, including fungal infection, bacterial invasion, and virus attack (Chaouch et al, 2010 ; Liu et al, 2020a ; Qi et al, 2012 ). During the long‐term evolution of the arms race with pathogens, plants have evolved sophisticated defence mechanisms to effectively ward off different kinds of pathogens (Li et al, 2020b ; Song et al, 2021 ; Yuan et al, 2017 ). Based on lifestyles, plant pathogens can be generally categorized into biotrophic and necrotrophic pathogens, which derive nutrients mainly from living host tissues or dead/dying cells, respectively (Qi et al, 2012 ; Spoel & Dong, 2008 ).…”
Section: Introductionmentioning
confidence: 99%